2022
DOI: 10.9734/jpri/2022/v34i33a36123
|View full text |Cite
|
Sign up to set email alerts
|

Post-injection Complications. Nicolau Syndrome as a Consequence of Local Irritant Effects of Drugs, Including Antiseptics, Local Anesthetics, NSAIDs, Steroids and Anticoagulants

Abstract: It has been shown that some drugs considered to be of good quality today can cause an iatrogenic disease known as Nicolau syndrome. Nicolau syndrome is a rare cutaneous drug reaction occurring after injection many drugs. This disease has been found to be caused by the very strong local irritant activity of drug solutions. It turned out that the standard for assessing the quality of drug solutions does not include assessment of their osmotic activity and the strength of their local irritating effect on various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These complications are not caused by injection of any specific drug, and cannot be explained by the known mechanisms of drug action. Additionally, Nicolau syndrome can develop after injections of local anesthetics, steroids, nonsteroidal anti-inflammatory drugs, chemotherapeutic agents, vaccines, and a combination of drugs [ 20 , [36] , [37] , [38] , [39] ]. Tachon syndrome, similar to Nicolau syndrome, describes post-injection complications of steroid injection into an artery and vein [ [40] , [41] , [42] ].…”
Section: Introductionmentioning
confidence: 99%
“…These complications are not caused by injection of any specific drug, and cannot be explained by the known mechanisms of drug action. Additionally, Nicolau syndrome can develop after injections of local anesthetics, steroids, nonsteroidal anti-inflammatory drugs, chemotherapeutic agents, vaccines, and a combination of drugs [ 20 , [36] , [37] , [38] , [39] ]. Tachon syndrome, similar to Nicolau syndrome, describes post-injection complications of steroid injection into an artery and vein [ [40] , [41] , [42] ].…”
Section: Introductionmentioning
confidence: 99%
“…Our assumption is substantiated by the following recent discovery by Russian researchers. It has been shown that the local effect of various drugs from different pharmacological groups, developing in the first seconds and minutes during local interaction with tissues at the site of application, instillation or injection and causing local irritant, inflammatory and necrotic effects, is of a universal nature, not related to the specific pharmacological activity of the main ingredients [21]. Moreover, it has been shown that one of the causes of local irritant, inflammatory and necrotic effects of dosage forms (solid, liquid and gaseous) is their excessive physical-chemical aggressiveness due to excessive hypertonic and/ or hyperacidic activity by ignorance [21,22].…”
mentioning
confidence: 99%
“…It has been shown that the local effect of various drugs from different pharmacological groups, developing in the first seconds and minutes during local interaction with tissues at the site of application, instillation or injection and causing local irritant, inflammatory and necrotic effects, is of a universal nature, not related to the specific pharmacological activity of the main ingredients [21]. Moreover, it has been shown that one of the causes of local irritant, inflammatory and necrotic effects of dosage forms (solid, liquid and gaseous) is their excessive physical-chemical aggressiveness due to excessive hypertonic and/ or hyperacidic activity by ignorance [21,22]. The fact is that blood and most tissues of the human body have alkaline activity within pH 7.4 and osmotic activity within 280-300 mosmol/L of water, so it is alkaline and isotonic activity that is normal for most microorganisms that are human pathogens.…”
mentioning
confidence: 99%